Vloga zdravstvene vzgoje pri uživanju medikamentozne terapije bolnikov s psihotično motnjo v Psihiatrični bolnišnici Idrija - Sedej-Kodela, Andreja (Obzornik zdravstvene nege, 2008)
Introduction: Health education of patients is considered a significant segmentof their treatment. It is important that the health education is a wellplanned, documented, continuous and evaluated process. Through appropriatehealth education, the patient gains the necessary knowledge for safe and independent administration of medicine. The aim of the research was to point to the emerging need for health education regarding administration ofmedicamental treatment to patients suffering from psychotic disorders and establish the role of the nurses in this process. Methods: The research was conducted in January and February 2006 in six hospital wards of the Psihiatrična bolnišnica Idrija (PBI), where a sample of 87 hospitalized patients was gathered. The survey included 26 yes/no and multiple-choice questions with an additional open-type question. The research was carried out using the descriptive method. Results and discussion: 83 out of 87 questionnaires were returned. The sample included 37% women and 63% men. 82% of surveyed patients expressed a desire to gain knowledge about prescribed medicamental treatment. In more than 50% of the cases the information on illness, prescribed medicine and its side effects is given by the doctor, while nurses only provide 15-20% of information. Less than half of the patients are well acquainted with the side effects of medicines. The findings of the survey show that the patients wish to acquire this knowledge and that the nurses' role do health education in the area of medicamental treatment is insignificant and neglected, so there is a need in PBI to develop a relevant health education content for the target audience.
Keywords: Antipsihotiki; Antipsychotic Agents; Health Education; Psihiatrična nega; psihiatrija; Psihoze; Psychiatric Nursing; psychiatry and clinical psychology; Psychotic Disorders; therapy; zdravljenje; Zdravstvena vzgoja